Why does it rain? - Couchman, Simon; Couchman, Simon (Leicester, United Kingdom Fox Eye Publishing, 2023)
Young children are very curious about the world around them.They love to ask us lots of questions and expect adults to have all the answers.Do not worry as help is at hand.This colourful series of books will amuse whilst providing simple answers to their most common and difficult of questions
The World Around Us
Keywords: General Knowledge